2016
DOI: 10.5755/j01.eie.22.2.12177
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Determine Software Security Level using Bayes Classifier via Static Code Metrics

Abstract: Technological developments are increasing day by day and software products are growing in an uncontrolled way. This leads to the development of applications which do not comply with principles of design. Software which has not passed security testing may put the end user into danger. During the processes of error detection and verification of developed software, static and dynamic analysis may be used. Static code analysis provides analysis in different categories while coding without code compile. Source code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For example, the number of independent paths through source code provides the complexity of the code [25]. If there is a high number of if-statements and loops in a source code, then cyclomatic complexities are more likely to occur, which can also affect the security of a program [26]. A number of studies have found that increased complexity in systems is the main reason for vulnerabilities to arise in software systems [26][27].…”
Section: Security Bad Smellmentioning
confidence: 99%
“…For example, the number of independent paths through source code provides the complexity of the code [25]. If there is a high number of if-statements and loops in a source code, then cyclomatic complexities are more likely to occur, which can also affect the security of a program [26]. A number of studies have found that increased complexity in systems is the main reason for vulnerabilities to arise in software systems [26][27].…”
Section: Security Bad Smellmentioning
confidence: 99%
“…Software Metrics use measurable software attributes as indicators of latent software quality attributes [21][22][23]. Detrition of quality created by presence of code smells can be quickly detected by using one or more related software metrics [24][25][26]. The literature survey identified that around 49 software metrics are applicative in code smell detection.…”
Section: Building Code Smell Repositorymentioning
confidence: 99%
“…2) Cyclomatic complexity arises because of a high number of loops and if statements. It has been found that cyclomatic complexity has a direct influence on security [29]. 3) Cognitive complexity can be discovered by observing the behavior of users finding a solution to a particular task or problem.…”
Section: Software Complexitymentioning
confidence: 99%